Innovation of science student worksheet on biology material to enhance junior high school students’ critical thinking skills - Fahmi Fahmi; Hery Fajeriadi; Yudha Irhasyuarna; Yuyun Eka Yulianti; Herman Herman (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Most of the worksheets currently used by students are unable to develop their critical thinking skills due to misconceptions about the content, a lack of meaningful activities, and incompatibility with the demands of the 21st century curriculum. This study aims to test the effectiveness of science worksheets on biology material in improving students' critical thinking skills. The study uses a formative evaluation approach with the Tessmer model, which consists of five stages: self-evaluation, expert review, one-to-one evaluation, small group, and field test. Data collection was conducted using validation instruments, observation sheets, and critical thinking skill tests. The results of the study indicate that the developed student worksheets are very valid, practical, and effective in enhancing students' critical thinking skills in learning science concepts in biology. Thus, these developed student worksheets have the potential to be used in science education for biology topics. These findings highlight the potential of such worksheets as an alternative learning tool aligned with the curriculum and 21st-century competencies, offering conceptual and practical value for enhancing effective science education that improves students' critical thinking skills.Abstrak. Sebagian besar lembar kerja peserta didik yang digunakan saat ini belum mampu mengembangkan keterampilan berpikir kritis siswa karena miskonsepsi konten, minimnya aktivitas bermakna, dan ketidaksesuaian dengan tuntutan kurikulum abad ke-21. Penelitian ini bertujuan untuk menguji hingga efektivitas lembar kerja peserta didik IPA pada materi biologi dalam meningkatkan keterampilan berpikir kritis peserta didik. Penelitian menggunakan pendekatan evaluasi formatif dengan model Tessmer yang terdiri atas lima tahapan, yaitu self-evaluation, expert review, one-to-one evaluation, small group, dan field test. Pengumpulan data dilakukan melalui instrumen validasi, lembar observasi keterlaksanaan, dan tes keterampilan berpikir kritis. Hasil penelitian menunjukkan bahwa lembar kerja peserta didik yang dikembangkan memperoleh kategori sangat valid, praktis, dan efektif dalam meningkatkan keterampilan berpikir kritis peserta didik dalam belajar konsep IPA pada materi biologi. Dengan demikian, lembar kerja peserta didik yang dikembangkan ini berpotensi untuk digunakan dalam pembelajaran IPA materi biologi. Temuan ini menyoroti potensi lembar kerja semacam itu sebagai alat pembelajaran alternatif yang selaras dengan kurikulum dan kompetensi abad ke-21, menawarkan nilai konseptual dan praktis untuk meningkatkan pendidikan sains yang efektif meningkatkan keterampilan berpikir kritis peserta didik.